Prevalência de lipodistrofia em pessoas vivendo com HIV atendidos em Tubarão, Santa Catarina - Silva, Maricele Almeida da (2016)
Introduction: HIV-associated lipodystrophy syndrome is a major adverse effect of highly active antiretroviral therapy (HAART), although it also occurs among people living with HIV who do not receive any pharmacological treatment. Lipodystrophy diminishes patients’ quality of life and may hinder treatment compliance or lead to its abandonment. Objective: To estimate the prevalence of lipodystrophy and associated factors in individuals living with HIV. Methods: Cross-sectional study conducted from October 2015 to March 2016. A sample was recruited from individuals living with HIV who attended an outpatient clinic in Tubarão, state of Santa Catarina, Brazil. We collected information on demographics, lifestyle, HIV infection, and clinical aspects. Lipodystrophy was diagnosed through patient self-report associated with anthropometry. Results: We surveyed 405 patients (most were white men; mean age 43.7 years). The mean duration of HIV infection was 74.6 months, and 90.1% of the respondents were taking antiretroviral therapy. The prevalence of lipodystrophy was 34.2%, of whom 43% had lipoatrophy, 52% had lipohypertrophy, and 5% had a mixed form. There was a statistical association between the presence lipodystrophy and female gender [OR = 1.77 (95% CI 1.35 to 2.32)] and the duration of HIV infection ([OR = 1.00 (95% CI 1.00 to 1.04)]. Conclusion: Lipodystrophy was prevalent in more than one-third of the surveyed subjects, which is a warning signal. Lipodystrophy affects quality of life and adherence to treatment, and may cause cardiovascular damage in this population.